Geochemical and petrological studies of high sulfur coal and overburden from Makum coalfield (Northeast India) towards understanding and mitigation of acid mine drainage - Angana Mahanta; Debashis Sarmah; Nilotpol Bhuyan; Monikankana Saikia; Sarat Phukan; K. S. V. Subramanyam; Ajit Singh; Prasenjit Saikia; Binoy K. Saikia (International Journal of Coal Science & Technology, 2024)
Abstract Opencast coal mining produces trash of soil and rock containing various minerals, that are usually dumped nearby the abandoned sites which causes severe environmental concern including the production of acid mine drainage (AMD) through oxidation pyrite minerals. The current study entailed assessing the potential production of AMD from an opencast coal mining region in Northeast part of India. In order to have a comprehensive overview of the AMD problem in Makum coalfield, the physico-chemical, geochemical, and petrological characteristics of the coal and overburden (OB) samples collected from the Makum coalfield (Northeast India) were thoroughly investigated. The maceral compositions reveal that coal features all three groups of macerals (liptinite, vitrinite, and inertinite), with a high concentration of liptinite indicating the coal of perhydrous, thereby rendering it more reactive. Pyrite (FeS2) oxidation kinetics were studied by conducting the aqueous leaching experiments of coal and (OB) samples to interpret the chemical weathering under controlled laboratory conditions of various temperature and time periods, and to replicate the actual mine site leaching. Inductively coupled plasma-optical emission spectroscopy (ICP-OES) was operated to detect the disposal of some precarious elements from coal and OB samples to the leachates during our controlled leaching experiment. The Rare earth element (REE) enrichment in the samples shows the anthropogenic incorporation of the REE in the coal and OB. These experiments reveal the change in conductivity, acid producing tendency, total dissolved solid(TDS), total Iron(Fe) and dissolved Sulfate(SO4 2−) ions on progress of the leaching experiments. Moreover, the discharge of FeS2 via atmospheric oxidation in laboratory condition undergoes a significant growth with the rise of temperature of the reaction systems in the environment and follows pseudo first order kinetics. A bio-remediative strategies is also reported in this paper to mitigate AMD water by employing size-segregated powdered limestone and water hyacinth plant in an indigenously developed site-specific prototype station. Apart from neutralisation of AMD water, this eco-friendly AMD remediation strategy demonstrates a reduction in PHEs concentrations in the treated AMD water.